The Feasibility of using Natural Rocks as Sources of Iron, Manganese and Copper in Livestock Feeding in Ethiopia (Global Journal of Science Frontier Research, 2015)
In Ethiopia, feed industries are widely using limestone as a cheap source of Ca without considering the source variability's and the amount of other minerals without adequate information on the bioavailability of its Ca content and the presence of other toxic minerals. This being the case, the present study was conducted to determine the iron, Manganese and copper content of samples of limestone , marble powder and gypsum collected from different parts of Ethiopia. Adequate quantities of lime stone, marble powder and gypsum were procured from different parts of Ethiopia and subjected to laboratory chemical analysis in triplicate. The results of this study clearly showed that the total ash content of all the materials analyzed in this study ranged between 81 and 99%, indicating the potential use of these materials (limestone, marble powder and gypsum) collected from different part of Ethiopia as supplementary mineral feed source in very small amounts.
Keywords: calcite powder; lime stone; livestock; marble powder; minerals